The Accountability Practices Of A Corporatist Waqf Institution In Malaysia - Abdul Wahab, Ainol Basirah (2024)
This study aims to examine the internal and external accountability practices in a corporatist waqf institution in Malaysia in light of its complex institutional arrangement. Internal accountability is defined as the accountability to achieve the social and commercial development mission, while external accountability is defined as the accountability to the external stakeholders (the upward and downward stakeholders).